2020
DOI: 10.1155/2020/3481758
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxy-α-sanshool Possesses Protective Potentials on H2O2-Stimulated PC12 Cells by Suppression of Oxidative Stress-Induced Apoptosis through Regulation of PI3K/Akt Signal Pathway

Abstract: Zanthoxylum bungeanum pericarp is a commonly used herbal medicine in China with effects of anti-inflammatory and analgesic, improving learning and memory ability, while hydroxy-α-sanshool (HAS) is the most important active ingredient of Z. bungeanum pericarps. The purpose of this study was to investigate the neuroprotective effect of HAS and its related possible mechanisms using a H2O2 Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 42 publications
4
41
0
1
Order By: Relevance
“…The mitochondrial-dependent apoptosis is one of the most important pathways for cell death, and proteins in caspase and Bcl-2 families are the dominant regulators in this apoptotic pathway [ 19 , 20 ]. The results of our present study ( Figure 4(a) ) revealed that RTF treatment (8 and 16 μ M) could statistically upregulate the cleaved caspase family proteins (cleaved caspase-3, cleaved caspase-8, and cleaved caspase-9) and proapoptotic Bcl-2 family proteins (Bax and Bim), while statistically downregulating the antiapoptotic Bcl-2 family proteins (Bcl-2 and Bcl-xL) compared to the control cells.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mitochondrial-dependent apoptosis is one of the most important pathways for cell death, and proteins in caspase and Bcl-2 families are the dominant regulators in this apoptotic pathway [ 19 , 20 ]. The results of our present study ( Figure 4(a) ) revealed that RTF treatment (8 and 16 μ M) could statistically upregulate the cleaved caspase family proteins (cleaved caspase-3, cleaved caspase-8, and cleaved caspase-9) and proapoptotic Bcl-2 family proteins (Bax and Bim), while statistically downregulating the antiapoptotic Bcl-2 family proteins (Bcl-2 and Bcl-xL) compared to the control cells.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the unlabeled quantitative proteomics analysis was carried out to explore the deep possible mechanisms of antitumor effects of RTF, and the related KEGG analysis based on differential proteins revealed that PI3K/Akt and MAPK signaling pathways might be related to the antitumor effects of RTF (data not shown). Previous scientific reports demonstrated that PI3K/Akt and MAPK signaling pathways are also closely involved in the ROS-induced mitochondrial-dependent apoptosis [ 19 , 26 , 27 ]. Consequently, we examined the related proteins in the two signal pathways and found that RTF treatment could downregulate the phosphorylation of PI3K, Akt, and ERK, while upregulating the phosphorylation of JNK in HeLa cells.…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondrial function is important for the survival of cells, and the decreased mitochondrial membrane potential (MMOP, Δ Ψ ) could induce the apoptosis of cells. 43 , 44 In addition, the flow cytometry analysis with fluorescent double staining is another important way for determining the apoptosis in cells. 45 The results of this study showed that GSZD could reduce the MOMP in MH7A cells, and increase the level of apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…AKT also known as protein kinase B, is activated by various stimuli, growth factors and hormones (Risso et al 2015;Song et al 2019). It has been reported that Akt plays a crucial role in cell survival and development (Li et al 2020), and the activation of AKT is involved in regulating the proliferation and migration of hASMC (Deng et al 2017;Lin et al 2019). A previous study demonstrated that AKT activation was significantly increased in hASMC induced by TGF-β1, while inhibition of the AKT signaling pathway significantly decreases hASMC migration (Lv et al 2019).…”
Section: Discussionmentioning
confidence: 99%